Pembuatan Dan Pengembangan Website Desa Lepak Timur Kecamatan Sakra Timur Kabupaten Lombok Timur Sebagai Upaya Pengabdian Masyarakat - Mahpuz; Muhamad Sadali; holis, olis; Wisnu Al Korni; Azril Miqraji; Zulkifli (Universitas Hamzanwadi, 2025)
A village website is a digital innovation aimed at simplifying community complaints and ensuring transparent access to information. This article discusses the development of a village website as a medium for community complaints, focusing on the stages of planning, implementation, and evaluation. The designed website features include a complaint form, village profile, and public information. Evaluation results indicate that the website functions effectively and helps the community to express aspirations more easily and quickly. Specifically, the purpose of this website is for transparency of the village government regarding the provision of information about the village government's work program as a whole openly to the community, improving public services regarding citizen access to village administration services, means of communication and information between the village government and its citizens, promoting village potential by displaying local potential owned by the village, increasing community participation to take part in planning, implementing and evaluating village programs, digitalizing village administration to reduce dependence on manual processes with digital systems. Web-based information systems not only support the delivery of information, but also facilitate integrated village data management. This system can reduce human error, increase work efficiency, and provide up-to-date information. for the community